1902 Ohio Gen. and Local Acts 23, Extraordinary Sess., An Act to Provide for the Organization of Cities and Incorporated Villages . . . and to Repeal All Sections of the Revised Statutes Inconsistent Herewith, § 7, pt. 11 (vol. 96) - (:unkn) unknown (General Publisher, 1902)
To regulate the transportation, keeping and sale of gunpowder and other explosives or dangerous combustibles and materials and to provide or license magazines for the same.
--
Keywords: TRANSFER; MANUFACTURE & STORAGE OF GUNPOWDER